Agent-Based Modeling: An Innovative Opportunity for Population-Based Oral Health Promotion - Maryam Sadeghipour; Peyman Shariatpanahi; Arezoo Ebn Ahmady; Mohammad Hossein Khoshnevisan (Tehran University of Medical Sciences, 2016)
---